2020
DOI: 10.3390/foods10010031
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera: An Unknown Crop in Developed Countries with Great Potential for Industry and Adapted to Climate Change

Abstract: Moringa oleifera is originally a tropical crop with a fast development, little known in developed countries but cultivated since ancient times. It can adapt to regions affected by climate change, such as the Mediterranean basin, since it is a crop with a great resistance to high temperatures. In this study an in-depth bibliographical review was carried out by consulting different databases (Science Direct, FSTA, Scielo, Riunet, and Google Scholar) in order to find published scientific studies on the characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 41 publications
1
57
0
1
Order By: Relevance
“… 2 and Trigo et al . 17 . Quercetin, myricetin glycosides, caffeoylquinic acid, coumaroylquinic acid, hydroxybenzoic acid, kaempferol, glucotropaeolin, glucosinalbin, glucoraphanin, glucomoringin, glucoiberin, glucosinolates, apigenin, luteolin, lutein, luteoxanthin, zeaxanthin, b-carotene and isothiocyonates were identified as the main compounds in the extracts from moringa 2 , 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“… 2 and Trigo et al . 17 . Quercetin, myricetin glycosides, caffeoylquinic acid, coumaroylquinic acid, hydroxybenzoic acid, kaempferol, glucotropaeolin, glucosinalbin, glucoraphanin, glucomoringin, glucoiberin, glucosinolates, apigenin, luteolin, lutein, luteoxanthin, zeaxanthin, b-carotene and isothiocyonates were identified as the main compounds in the extracts from moringa 2 , 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…USDA FoodData Central has shown that 100 g of raw leaves, for example, containing carbohydrate (≈8.28 g), protein (≈9.4 g), lipid (≈1.4 g), vitamins (A equiv., ≈378 µg; various Bs; C, ≈51.7 mg; folate, ≈40 µg), minerals (potassium, ≈337 mg; calcium, ≈185 mg; magnesium, ≈42 mg; iron, ≈4 mg), and dietary fiber (≈2 g) [59]. The analysis of dried MO demonstrated that leaves are a rich source of omega-3 and omega-6 polyunsaturated fatty acids and various phytochemicals [58,60]. The relatively wide range of variability in nutritional data was also reported, mainly due to genetic background, soil, climate, season, and plant; the use of different procedures of processing and storage and analytical techniques may also increase the variations [61-64].…”
Section: Nutritional Characteristics Of Momentioning
confidence: 99%
“…Moreover, such specificity of action of lurbinectedin allows the identification of active genes involved in tumorigenesis and in neuroendocrine reprogramming of the cell. This new drug has completely changed the therapeutic landscape of SCLC since its recent accelerated approval as a monotherapy in metastatic disease by the FDA (Kepp et al , 2020 ; Shinn et al , 2020 ; Trigo et al , 2020 ; Baena et al , 2021 ; Cortinovis et al , 2021 ; Singh et al , 2021 ). This work provides important molecular information underlying its efficacy.…”
Section: Discussionmentioning
confidence: 99%